Prenatally diagnosed TTN mutation with repeated bilateral club foot by whole exome sequencing - Shim, So Hyun; Kim, Ji Youn; Sung, Se Ra; Park, Ji Eun; Shin, Yun Jeong; Shim, Sung Han; Cha, Dong Hyun (Biochip journal, 2017)
With significant advances in genomic technologies over recent years, Next-generation sequencing (NGS) has become an important tool not only for gene discovery and research but also for clinical genetic diagnosis of rare disorders and single-gene-disorder analysis. Many hundreds of single-gene disorders have been described that can manifest prenatally and will comprise a large portion of undiagnosed, chromosomally normal cases but underlying cause of the abnormality still remains unknown for the large majority of cases with an abnormal ultrasound. However, there has been little experience and study in using trio whole exome sequencing (WES) for prenatal diagnosis. In this report the NGS method was applied for the prenatal genetic diagnosis of unidentified life-threatening phenotype in one family and confirmed the pattern of inheritance of titinopathy as well as two novel TTNgene variations. The report presented in these pages offers a unique and valuable perspective on relevance and feasibility of NGS in prenatal diagnosis field.